Central and peripheral analgesic active components of triterpenoid saponins from Stauntonia chinensis and their action mechanism - Gong, Ji-Hong; Zhang, Chang-Ming; Wu, Bo; Zhang, Zi-Xun; Zhou, Zhong-Yan; Zhu, Jia-Hui; Liu, Han; Rong, Yi; Yin, Qian; Chen, Ya-Ting; Zheng, Rong; Yang, Guang-Zhong; et al. (Frontiers in Pharmacology, 2023)
Triterpenoid saponins from Stauntonia chinensis have been proved to be a potential candidate for inflammatory pain relief. Our pharmacological studies confirmed that the analgesic role of triterpenoid saponins from Stauntonia chinensis occurred via a particular increase in the inhibitory synaptic response in cortex at resting state and the modulation on capsaicin receptor. However, its analgesic active components and whether its analgesic mechanism are limited to this are not clear. In order to further determine its active components and analgesic mechanism, we used patch clamp technique to screen the chemical components that can increase inhibitory synaptic response and antagonize transient receptor potential vanilloid 1, and then used in vivo animal experiments to evaluate the analgesic effect of the selected chemical components. Finally, we used patch clamp technique and molecular biology technology to study the analgesic mechanism of the selected chemical components.The results showed that triterpenoid saponins from Stauntonia chinensis could enhance inhibitory synaptic effect and antagonize transient receptor potential vanilloid 1 through different chemical components, and produce central and peripheral analgesic effects. The above results fully reflect that "traditional Chinese medicine has multi-component, multi-target and multi-channel synergistic regulation".